Evaluasi Penegakan Hukum Pelindungan Pekerja Migran Indonesia Berbasis Legal Consciousness Theory Pasca : Undang-Undang Nomor 18 Tahun 2017 tentang Pelindungan Pekerja Migran Indonesia - Hilyatul Asfia (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to evaluate law enforcement related to the protection of Indonesian Migrant Workers (PMI) after the enactment of Law No. 18 of 2017 using the Legal Consciousness Theory approach. The main problem formulation raised is how the implementation of the law is in practice and what obstacles arise in the implementation of the legal protection. The research method used is a qualitative method with a juridical-sociological approach, through the collection of primary data (interviews with relevant stakeholders) and secondary data (document and literature studies). The results of the study indicate that although normatively Law No. 18 of 2017 has provided a better protection framework, in practice there are still various obstacles, such as low levels of legal awareness of PMI, weak government supervision, and overlapping regulations. The legal awareness of PMI tends to be at the level before the law or with the law, which means they still see the law as something that is far away and not always accessible. Therefore, efforts are needed to strengthen legal capacity, increase socialization, and more effective supervision to ensure that legal protection for PMI can be implemented optimally.